Morfologia e composição de zircão de rochas ígneas do Terreno Granito-Greenstone de Rio Maria, Cráton Amazônico, através de microscopia eletrônica de varreduracatodoluminescência (MEV-CL) - RAMALHO, Ishi Macris de Oliveira (Universidade Federal do Pará, 2019)
Zircons of Archean TTG rocks, represented by Arco Verde Tonalite (2,97-2,93 Ga), Mogno Trondhjemite (2,97-2,96 Ga), Mariazinha Tonalite (2,92 Ga), Água Fria Trondhjemite (2,86 Ga), Rio Maria (2,87 Ga), Trairão and Grotão granodiorites and Guarantã leucogranite (2,87 Ga), beyond the São João paleoproterozoic granite (1,89 Ga), outcropping in the Rio Maria Granite-Greenstone Terrene, southeastern portion of the Amazonian Craton, were studied by cathodoluminescence images (CL) and semiquantitative analysis of EDS (Energy Dispersive Spectroscopy) in a scanning electron microscope (SEM). The internal textural features observed by CL images showed complex stories of crystallization for zircons of different groups of rocks such as: (1) euhedral crystals, strongly zoned without evident alteration and subhedral to anhedral crystals, weakly zoned and intensely altered; (2) crystals showing well defined oscillatory zoning and homogeneous crystals or with imperceptible zones, showing changes in physical and chemical conditions during crystallization; (3) crystals with Ca and U metamict enriched cores and crystals with luminescent cores resembling inherited cores; (4) zircon crystals containing several F-apatite inclusions that truncate or accompany their growth zones, indicating that apatite is a mineral phase as early as zircon in the history of crystallization of their host rocks; (5) crystals devoid of F-apatite inclusions, which could indicate compositionally different source in relation to rocks containing apatite inclusions; (6) zircons crystals with more luminescent edges than their inner portions, suggesting compositional change at the end of crystallization. Temporal and geochemically distinct granitoids were individualized and characterized in specific geochemical diagrams based on the Zr, Hf, Y, Nb and Ta content of their zircons. Zircons of the São João paleoproterozoic granite showed a distinct geochemical signature from those of TTG Archean rocks, indicating that these rocks can be individualized through composing of their zircons, even through semiquantitative analyzes of EDS. SEM-CL-EDS studies in zircons crystals are important tools in the characterization of different groups of igneous rocks and provide complementary information to petrological studies.